Assembly and programming of a micro-compression platform with in-situ imaging system - Lee, Judy Qian Hui. (2010)
Materials are compressed with the objective of determining their mechanical properties, when subjected to various loads. While ductile materials have no definite compressive strength, brittle materials depend greatly on compression test for its elastic and compressive fracture measurement. Current market designs of compression tester are largely for heavy duty purposes, limited tester cater for micro-compression test. Moreover, the market designs are lacking in important functions such as capturing image of the specimen-under-test for better analysis of the material. Hence, the project of designing a micro-compression setup fixed on a 3-D translation stage with displacement actuator, load cell and imaging system was initiated. By designing and fabricating some of the hardware parts, coupled with the purchase of necessary equipments, a micro-compression set-up was built. The system is capable of compressing up to a load of 44.5N, from just 0.05μm to 25mm with a velocity of up to 1.5mm/sec. The image capturing system has a resolution of 2452 (H) x 2054 (V) and a frame rate of 15fps and provides magnification up to 250X. After assembling all the components, a program was written for the system. The program controls the devices and provides readings and images during the compression test. However, the system has its own limitations in the limited range of velocities and unstable sampling rate. This report will present the insights on the design and programming of the micro-compression system as well as providing a peek of what the system can offer in terms of the test results, lastly, the report will discuss the limitations and improvement of the system.